Medical conduct and knowledge about physical activity counseling in the largest hospital complex in Latin America - Reiss, Débora Borowiak; Lemes, Ítalo Ribeiro [UNESP]; Roschel, Hamilton; Gualano, Bruno (Elsevier, 2025)
OBJECTIVE: To characterize practices and knowledge regarding PA counseling at a large tertiary hospital. DESIGN: Cross-sectional observational study. PARTICIPANTS AND SETTING: Physicians with an active medical practice within the university hospital were invited to respond to an online survey. INTERVENTIONS: A questionnaire designed to capture information on medical training, life habits and knowledge about PA. MAIN OUTCOMES MEASURES: Sedentary behavior, clinical practice and self-efficacy were assessed by Likert-type questions, whereas regular practice, previous training, and knowledge of PA were evaluated through dichotomous questions (answers: "yes or no" or "true or false"). RESULTS: Response rate was 11.5 % (50.6 % female, 44.9 ± 12.8 years), 67.7 % were physically active, and 63.3 % had 4 to 8 h/day of sedentary behavior. Only 40.7 % had previous training on PA, 99.7 % recognized the importance of recommending PA, but only a small part (48.4 %) recommended PA in all consultations (the main barrier was lack of specific training). In addition, 69.2 %, 58.7 % and 65.5 % rated their abilities to collect PA history, assess contraindications, and engage the patient as good/excellent, respectively. Knowledge of PA was rated as low to very low, with correct answers ranging from 49 % to 17 % and as low as ∼10 % (when considering the pediatric population). CONCLUSION: Although physicians recognize the importance of PA counseling and have high perceived self-efficacy in relation to counseling skills, few put them into practice. This may be due to insufficient training on PA and/or the complexity of services provided at the tertiary hospital. The present results corroborate the need for improvements in medical training on PA.